Knowledge and attitude of polycystic ovary syndrome (pcos) among women who attend the outpatient clinics at Hospital Universiti Sains Malaysia (USM) - Zukiman, Siti Nur Zubaidah (Universiti Sains Malaysia, 2024)
Polycystic ovary syndrome (PCOS) is a common metabolic and endocrine disorder in females in their reproductive-age and is associated with some clinical complications. The study aims to assess the level of knowledge and the level of attitude on polycystic ovary syndrome (PCOS) among women who attend the outpatient clinics in Hospital Universiti Sains Malaysia (USM). A cross-sectional study was conducted on women aged 18 to 60 years old. Data was collected using a self-administered questionnaire. 165 women who fulfilled the inclusion criteria of this study was selected to answer the questionnaire. They were selected through convenience sampling method. Data collected were statistically analyzed using the SPSS software version 27. The study used descriptive statistics and Pearson Chi-square. The results show that 118(78.7%) of participants have a moderate level of knowledge on PCOS and 95(63.3%) of participants have moderate level of attitude on PCOS. There was no association between knowledge score and attitude score (p = 0.148), the result shows only 14(26.4%) of participants have good knowledge and positive attitude. Lastly, there was no association between sociodemographic factors [age (p = 0.222), marital status (p = 0.912), educational level (p = 0.743), occupational status (p = 0.442)] and the level of knowledge on PCOS. In conclusion, the level knowledge and attitude on PCOS among women must be enhanced and improved so that they are more knowledgeable regarding PCOS and it can help them to spread the risk and complication towards PCOS.